Use of sialic acid analogues to define functional groups involved in binding to the influenza virus hemagglutinin - Kelm, Sørge; Paulson, James C.; Rose, Ursula; Brossmer, Reinhard; Schmid, Walther; Bandgar, Babasaheb P.; Schreiner, Erwin; Hartmann, Michael; Zbiral, Erich (EJB, 1992)
The initial step of influenza infection is binding of the virus particles via their hemagglutinin to cell-surface sialic acids. This study was initiated to elucidate the functional groups of the nine-carbon sialic acid molecule which interact with the hemagglutinin and contribute to the affinity of this sugar to the protein. In order to address this question, synthetic sialic acid analogues were tested in a virus adsorption inhibition assay for their inhibitory potency. Modifications in three regions of the sialic acid molecule were evaluated: the glycerol side chain (C7 - C9), the N-acetyl group at C5, and the carboxy group (C1). In the glycerol side chain, the hydroxy groups at C7 and C8 appear to be important for binding through hydrogen bonds, whereas the hydroxyl at C9 does not appear to be involved. The N-acetyl group is critical for the interaction of sialic acid with the hemagglutinin. The results suggest that its contribution is mediated through hydrophobic interactions of the methyl group. Finally, the orientation of the carboxy group is essential for the binding of sialic acid to the hemagglutinin. The information gained in this study will be useful in developing novel compounds which bind more avidly to the influenza virus hemagglutinin. Such a strategy may contribute to the design of new anti-influenza drugs.
Elektronische Reproduktion der Druck-Ausgabe 3. März 2005
Gesehen am 24.06.2024